Isolation and Properties of a Temperature-Sensitive Sporulation Mutant of Bacillus subtilis - Szulmajster, J. (1970)
A thermosensitive sporulation mutant (t(s)-4) of Bacillus subtilis was isolated, and its morphological, physiological, and enzymatic properties were investigated. This mutant is able to grow equally well at 30 and 42 C, but is unable to sporulate at the higher temperature. Electron microscope studies have shown that the t(s)-4 mutant is blocked at stage zero of spore development. This was further confirmed by its inability to produce antibiotic when grown at the restrictive temperature and by the relatively low ribonucleic acid (RNA) and protein turnover during the stationary growth phase, characteristic for stage zero asporogenic mutants. At the permissive temperature, however, antibiotic production and RNA and protein turnover took place at the rate normally found in sporogenic strains of B. subtilis. The above properties were not altered in the parent strain when grown at either 30 or 42 C. By shifting cultures of the t(s)-4 mutant from 30 to 42 C and from 42 to 30 C at different stages of growth, we have been further able to show that the event affected at the high temperature takes place at a very early stage of spore development. As a consequence of this early block in the sporulation process, the t(s)-4 mutant grown at 42 C became defective in the late spore-specific enzymes involved in the biosynthesis of dipicolinic acid. This study suggests that the sporulation process is mediated by a regulatory protein which is altered in the thermosensitive mutant when grown at the restrictive temperature. As a result of this alteration, a pleiotropic phenotype is produced which has lost the ability to catalyze the late biochemical reactions required for spore formation.